MEDIA ALTERNATIF CAMPURAN DAUN PISANG KERING DAN KULIT JAGUNG UNTUK MENINGKATKAN PRODUKTIVITAS JAMUR MERANG (VOLVARIELLA VOLVACEA (BULL) SINGER.) DALAM KERANJANG - Suparti, Suparti; Safitri, Wardani Ana (Universitas Muhammadiyah Surakarta, 2020)
The growth of mushroom requires nutrients such as cellulose, hemicellulose and lignin which can be obtained from rice straw. However, the availability of rice straw at certain times is difficult to obtain. Dried banana leaves and corn husk have the potential to be used as alternative growing media because they contain cellulose, hemicellulose and lignin for the growth of mushrooms. This research was conducted to determine the productivity of straw mushrooms on a mixture of dried banana leaf media and corn husk planted in a basked. The method used RAL (Completely Randomized Design) which consisted of one factor, namely a mixture of 500gr, 375gr, 250gr, 125gr, and 0gr corn shells with Ogr dried banana leaves, 125gr, 250gr, 375gr, and 500gr. Data were tested by one-way Anova analysis. The result showed that there was no effect of the mixture of dried banana leaves and corn husk on the productivity of straw mushrroms. Mushroom can grow on all treatments.